Rural Banditry and the Education Sector in Northwest and Northcentral Nigeria - Kaka Ali , Hannatu; Yusuf Danga, Jamiu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
In the aftermath of the mass kidnap for ransom of students from different schools in Niger and Kaduna states of Nigeria by armed bandits, there is an argument that rural banditry stifles education in these states. This is because not only has it led to the closure of many schools, but also that there is an indication that kidnapping of students is a new dimension to the lingering issue of banditry in Niger and Kaduna states. Few scholars have examined the link between banditry and educational stagnation in these regions. This is surprising, as violent armed groups have often focused on kidnapping of students as a means of sustaining threat of violence, securing global attention, obtaining ransom and projecting national security as weak to secure the citizens. Using the descriptive framework, this paper examines the connection between rural banditry and educational sector in Niger and Kaduna states, Nigeria. It reveals the complicated challenges faced by government and security officials in tackling the menace of banditry. The mass kidnap of students, a vulnerable group in the society has become a norm than the exception. This has implication for the education sector as schools in rural areas have been shut down and academic calendar affected, thereby exacerbating existing inadequacy of educational provision in rural areas of these states.